Porous bead-on-string poly(lactic acid) fibrous membranes for air filtration - Wang, Zhe; Zhao, Chuchu; Pan, Zhijuan (Journal of colloid and interface science, 2015)
[Display omitted] •A formation mechanism of the porous bead-on-string PLA fibers was proposed.•Correlation between bead morphology and pore structure of membrane were put forward.•Moderate beads size and quantity were conducive to the low pressure drop.•Nanopores on beads and ultrafine nanofiber contributed to high filtration efficiency.•Porous bead-on-string nanofibrous media showed excellent air filtration performance. Porous bead-on-string poly(lactic acid) (PLA) nanofibrous membranes (NMs) were fabricated by electrospinning, and the formation mechanism of the membranes was determined in this study. The PLA fibrous morphology, including the fiber diameter, bead size, number of beads, and surface structure of the beads, could be closely controlled by regulating the solvent compositions and the concentrations of the PLA solutions. The filtration performance, which was evaluated by measuring the penetration of sodium chloride (NaCl) aerosol particles with an average diameter of 260nm, indicated that the filtration efficiency and pressure drop for the resultant PLA membranes could be manipulated by modifying the morphology of the fibers. Moderate bead size and quantity contribute to the low pressure drop, and small fiber diameters and nanopores on the beads were conducive to high filtration efficiency. Furthermore, the NM formed from a 5wt% solution and a solvent mixture containing dichloromethane (DCM)/N,N-dimethylacetamide (DMAC) in a 10/1 ratio of PLA by weight exhibited excellent filtration efficiency (99.997%) and a low pressure drop (165.3Pa), which are promising characteristics for the membranes’ application as filters for respiratory protection, indoor air purification, and other filtration applications.